Use of Experimental Design to Evaluate the Effect of the Incorporation of Quartzite Residues in Ceramic Mass for Porcelain Tile Production - Silva,Karina Ruiz (2019)
The potential of using quartzite residues in the composition of an industrial ceramic mass for porcelain tile production was investigated through experimental design. Chemical, physical and microstructural analyses were accomplished to understand how the incorporation of quartzite residues affects the material, before and after sintering. Central composite design was used to analyze the effects of firing temperature (1143; 1160; 1200; 1240; 1257ºC) and residue content (1.76; 3; 6; 9; 10.24 wt.%) on the physical-mechanical properties of the material, and regression models correlating these factors to the response variables linear shrinkage, water absorption, apparent density and flexural strength were adjusted. Firing temperature had statistically significant effect on the response variables, so that the elevation of its levels contributed to the properties improvement. Residue content presented non-significant effect. In conclusion, specimens containing quartzite residues, up to 10.24 wt.%, sintered at 1240 and 1257ºC, fulfil the ISO 13006 requirements for porcelain tiles.